Correction: Electrochemically deposited nanocrystalline InSb thin films and their electrical properties (Journal of Materials Chemistry C (2016) 4 (1345-1350) DOI: 10.1039/C5TC03656A) - Hnida, K. E.; Baessler, S.; Mech, J.; Szacilowski, K.; Socha, R. P.; Gajewska, Marta; Nielsch, Kornelius; Przybylski, M.; Sulka, G. D. (Journal of Materials Chemistry C, 2019)
There was an error in eqn (3) which was reproduced from the literature and used for the interpretation of the results. The calculations (using the equations from an original work from 1987) were done according the correct version of eqn (3) presented below:. (Table Presented).
CRIS-Team Scopus Importer:2022-04-14